Effect of Financial Performance and Dividend Policy on Stock Prices in Banking Companies Listed on the Stock Exchange - Dwi Lestari A (Journal AGENCY, 2023)
This study aims to determine the effect of financial performance and dividend policy on stock prices in banking companies listed on the IDX. The population of this study is the banking sector companies, totaling 7 companies. This research was conducted using quantitative methods with the variables used in this research are Financial Ratios and Dividend Policy which are proxied by Return on Assets (ROA), Current Ratio (CR), Return on Equity (ROE), Debt to Equity Ratio (DER). , Dividend Payout Ratio (DPR). The data analysis technique used is multiple linear regression with the help of SPSS software version 20. The results of this study indicate that Return on Assets (ROA) has no effect on stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Which means that the level of a company's ability to generate profits has no effect on stock prices, Current Ratio (CR) has a positive effect on stock prices. Which means that the level of a company's ability to fulfill all its short-term obligations has an effect on stock prices, Return on Equity (ROE) has a positive effect on stock prices. Which means that the level of a company's ability to generate profits has an effect on stock prices, Debt to Equity Ratio (DER) has no effect on stock prices. Which means that the level of the company's ability to use owner's capital has no effect on the stock price, the Dividend Payout Ratio (DPR) has no effect on the company's stock price. Which means that the level of the company's ability to pay dividends has no effect on stock prices.